The woman in Latin American and Spanish literature essays on iconic characters - Bueno, Eva Paulino; André, María Claudia; Agosín, Marjorie (McFarland, 2012)
"Examines how both male and female writers portray Latin American women, reinterpreting the dynamics between the genders across boundaries and historical periods. Supported by recent theories in literary criticism, gender, and Latin American studies, this compendium provides a deep understanding of the role of women as conduits for the appreciation of their countries and cultures"--Provided by publisher.